Association between Psychosocial Factor and Risk of Musculosceletal Disorders in Productive Age Patient at RSUD Dr. Moewardi Surakarta - Dea Linia Romadhoni; Alinda Nur Ramadhani (P3M Universitas 'Aisyiyah Surakarta, 2021)
Musculoskeletal Disorders (MSDs) is a form of complaint that occurs in bones, joints, ligaments, tendons, and muscles. Globally, MSDs are the biggest single cause of health complaints among workers. The purpose of this study was to analyze psychosocial factors that can increase risk of MSDs in reproductive age patients. This study used an analytic observational study with cross-sectional design. A sample 0f 116 subject was selected for this study by fixed disease sampling. Data were collected by questionnaire and medical record, and analyzed by path analysis. Results: Risk of MSDs was directly related to with non-ergonomic work posture (OR: 2.35; CI 95%:1.44 to 3.26; P<0.001), there was indirect association with stress level variable (OR:0.79;CI 95%:0.01 to 1.58;P=0.047) which affected by type of work variabel (OR:0.83;CI 95%:0.87 to 1.58;P=0.029) and indirectly assaciated with bad work environment (OR:1.07;CI 95%:0.28 to 1.85;P=0.008).